2016
DOI: 10.1155/2016/4834579
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radiation Received by Slopes Using COMS Imagery, a Physically Based Radiation Model, and GLOBE

Abstract: This study mapped the solar radiation received by slopes for all of Korea, including areas that are not measured by ground station measurements, through using satellites and topographical data. When estimating insolation with satellite, we used a physical model to measure the amount of hourly based solar surface insolation. Furthermore, we also considered the effects of topography using the Global Land One-Kilometer Base Elevation (GLOBE) digital elevation model (DEM) for the actual amount of incident solar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…The model also estimates a more accurate solar insolation considering the surface slope and elevation by using the DEM data. In the previous study, the estimated solar insolation data were validated by using 37 ground station pyranometers and the results showed reliability for both clear and cloudy sky conditions [56]. Details of the physical model and validation results are described in Yeom et al [56].…”
Section: Coms Reflectance and Solar Insolationmentioning
confidence: 97%
See 1 more Smart Citation
“…The model also estimates a more accurate solar insolation considering the surface slope and elevation by using the DEM data. In the previous study, the estimated solar insolation data were validated by using 37 ground station pyranometers and the results showed reliability for both clear and cloudy sky conditions [56]. Details of the physical model and validation results are described in Yeom et al [56].…”
Section: Coms Reflectance and Solar Insolationmentioning
confidence: 97%
“…where ρ green , ρ red , and ρ nir are GOCI band 4 (green, 433-453 nm), band 5 (red, 650-670 nm), and band 8 (NIR, 845-885 nm) reflectances, respectively. The COMS MI data were used to estimate daily solar insolation with a spatial resolution of 1 km using the Kawamura [55] physical model modified by Yemo et al [56]. The model uses an improved cloud factor by using the visible reflectance and the solar zenith angle rather than the brightness temperature.…”
Section: Coms Reflectance and Solar Insolationmentioning
confidence: 99%
“…where S T , S I , S R , and S A are the total insolation, direct irradiance, diffuse irradiance due to Rayleigh scattering, and the diffuse irradiance due to scattering by aerosols, respectively. These parameters are used for the physical model of the satellite-based solar insolation [43]. The S T , S I , S R , and S A formulations are as follows:…”
Section: Climate Datamentioning
confidence: 99%
“…Furthermore, fewer surface stations are located in mountainous areas, yet SSI is highly dependent on topography and features larger temporal and spatial variations than horizontal surfaces [6]. Numerous attempts have been made at estimating SSI from satellite data on local or regional scales with multi-scale temporal resolutions in order to overcome the limitations of in situ records [7][8][9][10][11][12][13][14][15]. Perez et al (1997) demonstrated that satellite-derived irradiation is more accurate compared to interpolation techniques obtained from station measurements if the distance from the station exceeds 34 km for hourly irradiation and 50 km for daily irradiances [16].…”
Section: Introductionmentioning
confidence: 99%